The pelican brief - Grisham, John. (New York : Doubleday, 1992)
Two Supreme Court justices, one liberal and one conservative, are assassinated in one night. The country is stunned and baffled; the FBI has no clues. But Darby Shaw, a brilliant law student at Tulane, thinks she has the answer. Days of digging in the law library's computers have led her to an obscure connection between the two justices. She fleshes out her beliefs in a meticulous though wildly speculative brief that builds a strong case against a most unlikely suspect. But her suspect has powerful friends. One evening, outside a New Orleans restaurant, she narrowly escapes an assassin's car bomb. Someone has read her brief. Someone who wants her dead. She contacts investigative reporter Gary Grantham and convinces him that she's onto the biggest cover-up since Watergate. Together they go underground, trying to survive long enough to expose the real truth.--Adapted from dust jacket.
Two Supreme Court justices, one liberal and one conservative, are assassinated one night. The country is stunned and baffled; the FBI has no clues. But Darby Shaw, a brilliant law student at Tulane, thinks she has the answer. Days of digging in the law library's computers have led her to an obscure connection between the two justices. She fleshes out her beliefs in a meticulous though wildly speculative brief that builds a strong case against a most unlikely suspect. But her suspect has powerful friends. One evening, outside a New Orleans restaurant, she narrowly escapes an assassin?s car bomb. Someone has read her brief. Someone who wants her dead. She contacts investigative reporter Gary Grantham and convinces him that she's onto the biggest cover-up since Watergate. Together they go underground, trying to survive long enough to expose the real truth. -- Adapted from dust jacket.
Accelerated Reader
Keywords: Judges -- Crimes against -- Fiction; Women law students -- Fiction; Assassination -- Fiction; Journalists -- Fiction; Witnesses -- Fiction; Literature; Washington (D.C.) -- Fiction; Louisiana -- Fiction